Diesel cycle generator engine assisted by industrial automation systems (Industry 4.0) (Research, Society and Development, 2022)
Fuels such as biodiesel have been gaining popularity as an alternative fuel. The study deals with the evaluation of the performance and emissions of a generator engine operating with diesel and biodiesel blends, assisted by an industrial automation system used in Industry 4.0. The experiment was carried out in the laboratories of the State University of West Paraná. The energy generated, the specific consumption, the energy efficiency and the emissions generated by the generator set were evaluated during the experiment. The treatments used were type A petroleum diesel (D100), five blends (mixtures) of rapeseed biodiesel (B5, B10, B15, B20 and B50) and pure biodiesel (B100). The loads applied to the generator motor were of the 1.0 resistive type; 1.5; 4.5 and 6.0 kW for each fuel type. The generated energy kept increasing and stable as the load increased. The best result of specific consumption was with diesel (D100), followed by B10 and B20, both for the 4.5 kW load. Carbon monoxide gas emissions are reduced while carbon dioxide emissions increase with application of higher loads. Pure biodiesel (B100) tends to have better energy efficiency than the binary mixtures used when inserted at a load of 6.0 kW. The results obtained demonstrate that the blends of rapeseed biodiesel with conventional diesel are one of the possible viable solutions for the partial replacement of mineral diesel.